A correção de textos escolares em uma perspectiva enunciativa - Silva, Flávia Santos da (2020)
On this thesis, we consider the teaching of writing in schools and we analyze the correction of texts produced by students beyond the traditional aspects, such as prescriptive rules and pre-fixed models of orthographic and grammatical correction. It is done so because the textuality produced by students takes into account the use of language and signification, what demands from teachers acuity in their intervention, once writing, as a way of actualization of language, is a means for humans to live in society. It is taken into account Benveniste’s studies about enunciaton and it is discussed how it is possible to rethink the correction of texts in schools from his perspective on writing, as Benveniste does not have a specific theory for correction. It is sustained that texts must be produced to be read, not only to be evaluated. In such statement, there is the conception of correction that considers the functionning of writing and the meanings vehiculated. We make a conceptual experimentation of Benveniste’s theory, taking into consideration concepts as langue, parole, subject, discourse, signification, semiotics, semantics and enunciation. This conceptual experimentation provides the bases to discuss Benveniste’s conception of writing, which involves notions like written language, interior language, semiotic system, representation and designation. We analyze texts produced by students from the eighth year of Brazilian secondary school. We show that the corrections teachers make are orientated to orthographic, grammatical and genre aspects and we show how these corrections could be orientated to signification, taking into consideration what Benveniste calls discursive relation. For that, we suggest corrections to be made from an enunciative perspective, which allows to think about meaning and linguistic relations.